Meat and its meanings: representations of meat-eating in selected works of South African literature - Coetzer, Theo (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2016)
This thesis is situated within the burgeoning field of literary animal studies. Its aim is to analyse critically the way in which animals-as-meat are represented in South African literature. While meat pervades our lives and literature, there exists very little scholarship that considers literary depictions of meat. The thesis suggests that literary texts can offer useful reflections of the cultural environments in which they are immersed and, furthermore, can encourage what J. M. Coetzee calls the 'sympathetic imagination' in relation to animals. The dissertation offers close readings of three primary texts, while also drawing on a broader range of local fiction. Chapter 1 discusses Eben Venter's Trencherman, with a specific focus on Venter's use of the plaasroman and literary dystopia. Both genres are important to the novel's ubiquitous depictions of meat, serving to illustrate some of the destructive, and irreversible, excesses associated with traditional Afrikaner culture in South Africa. Meat consumption is not only depicted as being among these harmful excesses, but also comes to represent them collectively. Chapter 2 offers a reading of Zakes Mda's The Madonna of Excelsior, paying particular attention to its representation of the intersection between the objectification of women's bodies and the transformation of animals into meat. In my approach to this text, I make use of Carol J. Adams' notion of the 'absent referent'. I suggest that while Mda ostensibly considers the subjugation of both women and animals, the novel does not ultimately demonstrate concern for animals in their own right. The final chapter considers the representation of suffering in Damon Galgut's The Beautiful Screaming of Pigs. I argue that Galgut's text is alone among the three primary texts in its attention to the animal suffering inextricably linked to meat production. The novel depicts this suffering as being comparable to human suffering, while simultaneously demonstrating humans' indifference to their animal fellows. The dissertation concludes that while meat is infused with a range of meanings in South African literature, the most obvious and intrinsic one "“ the fact of animal death and animal suffering "“ is the one most often ignored.
Keywords: Uncatalogued